RESPONSE STRATEGIES ADOPTED BY PUBLIC UNIVERSITIES IN KENYA TO ENVIRONMENTAL AND MANAGERIAL CHALLENGES - MATHOOKO, FRANCIS MUTISO (My University, 2013)
The environment in which organizations operate is continuously changing, thereby posing challenges to organizations, and higher education institutions are no exception. The objective of this study was to understand how public universities in Kenya respond to environmental and managerial challenges and the factors that influence the choice of the response strategies. The study design was descriptive and utilized a cross-sectional survey of all the public universities in Kenya by administering a structured questionnaire to the top management team by mail and drop-and-pick-later methods. Additional primary data were collected through observations and interviews. Secondary data were collected from published works and, universities and government documents in public domain in order to corroborate the data collected from the primary sources. Statistical Package for Social Scientists (SPSS) was used to generate data that were analyzed using descriptive statistics. Content and logical analyses techniques were also used for data analysis. Positive responses were received from 63 respondents out of 91, yielding a 69.4% response rate. Of the respondents, 76% had basic training in the sciences and only 3% in business; 79% had no professional training in management and only 8% each had training at postgraduate diploma and postgraduate degree levels. The universities faced managerial challenges to a greater extent than they faced environmental challenges. The control function of management, and competitive and economic macro-economic factors posed the highest challenge. A significant difference (p<0.05) in the managerial and environmental challenges existed between new and old universities, and rural and urban universities. There was significant difference (p<0.05) and no significant difference (p<0.05) among the three categories of public universities (old, new and university colleges) in managerial and environmental challenges, respectively. The public universities adopted Porter’s generic competitive strategy model, of cost leadership, differentiation and focus to counter the challenges experienced, and in particular cost leadership and differentiation. The extent of adoption of differentiation strategy was significantly different (p<0.05) between the old and new universities and not among the three categories of public universities. Grand strategies adopted were diversification in related business, expansion and strategic alliances. The major operational strategies adopted included, management leadership in the formulation of response strategies, distributed leadership, benchmarking, and mounting of evening and weekend programmes. Some of the operational strategies adopted by some universities were, however, unethical and may compromise quality. Porter’s five competitive forces (PFCF) framework influenced the choice of response strategies adopted by the universities, particularly threat from new entrants, especially local private universities. The influence of the choice of the response strategies by PFCF framework was independent of the time the university was established and its status. Pressure from stakeholders, changes in government funding, reforms in the higher education sub-sector and location of the university also influenced the choice of response strategies. The results indicate that public universities in Kenya experience a multitude of environmental and managerial challenges and have adopted response strategies to cope with the challenges. The response strategies adopted and the factors influencing their choice are more or less similar to those applied by corporate organizations among them, grand strategies, Porter’s generic competitive strategy and PFCF framework. The results further indicate that the current public universities in Kenya are dependent on the environment in which they operate and, therefore, the study contributes to the environment-dependence theory of organizations.